(untitled) (European Journal of Marketing and Economics, 2023)
The final phases of the information systems lifecycle are no less important than the initial ones. However, previous research indicated a lack of studies on information systems discontinuance. This paper aims to verify whether this gap still exists by analysing the literature on enterprise resource planning (ERP) systems, a type of software widely used in many organisations. To identify the relevant literature, the paper involved searching in Scopus and Web of Science databases. Despite several ERP literature reviews suggesting more studies on the retirement phase and no time limits in the search, very few studies have been identified. To sketch the current state of knowledge on the selected topic, the paper developed a scoping review and, based on the results, comments on possible critical issues. The work supports researchers and practitioners interested in information systems discontinuance, as it provides some considerations to develop future research. In addition, it has practical implications because the advancement of the knowledge frontier will help organizations cope with this kind of change.